ANALISIS EFEKTIVITAS DAN KONTRIBUSI PAJAK DAERAH SEBAGAI SUMBER PAD KOTA SURABAYA - Novayati, Fenni; Idayati, Farida (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
This research is meant to analyze the effectiveness level and to find out the amount of local tax as the source of Local Own Source Revenue. The research object is local tax which has been collected by the government of Surabaya city in from 2011 to 2014. This research is qualitative research which is done by using secondary data source in the form of financial statement on the local tax revenue and the Local Own Source Revenue in 2011-2014 periods. The data collection has been done by conducting interview and documentation. The data analysis technique has been done by using the analysis of effectiveness level of local tax and the contribution analysis of local tax.The result of this research shows that the effectiveness level of local tax of Surabaya city includes the effectiveness criteria with the average effectiveness level each year is 96.25%. It can be stated that the government Surabaya city has succeeded in conducting the collection of local tax. The contribution of each local tax post to the Local Own Source Revenue city Surabaya city is in the category of very poor up to medium, in the other words the contributions of each local tax components is in the range of more than 0 percent up to 25 percents to the Local Own Tax.Keywords: Effectiveness level, contribution, local tax, Local own tax.